Exploring Work Readiness: The Role of Future Orientation Mediated by Career Self-Efficacy in University Students - Mutiara Mirah Yunita; Teguh Lesmana; D'aaron Q. Fallacorina (Psympathic : Jurnal Ilmiah Psikologi, 2026)
This study investigates the role of future orientation and career self-efficacy in shaping work readiness among university students. Using a cross-sectional survey design, data were collected from 321 students of a private university in Tangerang through validated questionnaires and analyzed with Structural Equation Modeling (SEM). The results show that future orientation does not have a significant direct effect on work readiness, whereas career self-efficacy has a positive and significant effect. Moreover, future orientation significantly influences career self-efficacy, which in turn mediates the relationship between future orientation and work readiness, indicating full mediation. These findings highlight the importance of strengthening students’ career self-efficacy as an internal resource to prepare them for the workforce. The study contributes to the understanding of psychological factors underlying work readiness and provides practical implications for career guidance and higher education.